Science and Justice The Massachusetts Witchcraft Trials - Fox, Sanford J. (Johns Hopkins University Press, 2019)
Originally published in 1968. Far from being an isolated outburst of community insanity or hysteria, the Massachusetts witchcraft trials were an accurate reflection of the scientific ethos of the seventeenth century. Witches were seldom hanged without supporting medical evidence. Professor Fox clarifies this use of scientific knowledge by examining the Scientific Revolution's impact on the witchcraft trials. He suggests that much of the scientific ineptitude and lack of sophistication that characterized the witchcraft cases is still present in our modern system of justice. In the historical context of seventeenth-century witch hunts and in an effort to stimulate those who must design and operate a just jurisprudence today, Fox asks what the proper legal role of medical science-especially psychiatry-should be in any society. The legal system of seventeenth-century Massachusetts was weakened by an uncritical reliance on scientific judgments, and the scientific assumptions upon which the colonial conception of witchcraft was based reinforced these doubtful judgments. Fox explores these assumptions, discusses the actual participation of scientists in the investigations, and indicates the importance of scientific attitudes in the trials. Disease theory, psychopathology, and autopsy procedures, he finds, all had their place in the identification of witches. The book presents a unique multidisciplinary investigation into the place of science in the life of the Massachusetts Bay Colony in the seventeenth century. There, as in twentieth-century America, citizens were confronted with the necessity of accommodating both the rules of law and the facts of science to their system of justice.